The effect of caffeine citrate on neural breathing pattern in preterm infants - Parikka, Vilhelmiina; Beck, Jennifer; Zhai, Qian; Leppäsalo, Juha; Lehtonen, Liisa; Soukka, Hanna (Early human development, 2015)
Caffeine citrate is widely used to prevent and treat prematurity-associated apnea. The aim of this study was to characterize the effect of caffeine citrate on the neural control of breathing, especially central apnea, in premature infants. Preterm infants were evaluated for 30min before and 30min after caffeine citrate loading (20mg/kg). A feeding tube including miniaturized sensors was used to measure the diaphragm electrical activity (Edi) waveform. Central apnea was defined as any period where the Edi waveform was flat for >5s. Seventeen preterm infants with a mean age of three days and mean birth weight of 900 grams were evaluated. In addition to central apnea, several parameters including neural inspiratory time, neural respiratory rate, peak Edi, delta inspiratory change in Edi (phasic Edi) and minimum Edi on exhalation were measured. The majority of the apnea were short (5 to 10s) and the number of apnea correlated with birth weight (p=0.039). Caffeine citrate reduced significantly the number of 5-to-10-second-long central apnea during the 30-minute periods (12±11 to 7±7; p=0.02). Caffeine citrate increased both peak and phasic Edi leading to a significant increase in the diaphragm energy expenditure. Edi signal can be reliably measured and processed to study changes in premature infants' neural breathing. The beneficial effect of caffeine citrate on the reduction of the number of apnea is mediated through stimulated neural breathing increasing the diaphragm energy expenditure. •Edi signal can be reliably measured to study premature infants' neural breathing.•Caffeine citrate reduces the number of central apnea in preterm infants.•Caffeine citrate increases peak and phasic electrical activity of the diaphragm.•Diaphragm energy expenditure is increased after caffeine citrate loading.